Analysis of the Hatch Cover Maintenance System on the Mv. Ocean Perkasa to Support Smooth Loading and Unloading Processes - I Komang Mahardhika Pratama; ⁠Haerani Asri; Sulastriani R; Subehana Rachman; Sigit Hendra Waskita (Sean Institute, 2026)
Hatch covers are vital components on the bulk carrier MV. Ocean Perkasa, functioning to maintain weathertightness to protect dry bulk cargo from damage. This study aims to determine the hatch cover maintenance system procedures and analyze their influence on the efficiency and smoothness of loading and discharging activities in port. The research method used is descriptive qualitative, with data collection techniques including direct observation, in-depth interviews with the Chief Officer, and documentation studies. The results of the study indicate that although maintenance followed the Planned Maintenance System (PMS), significant operational obstacles were still encountered. An incident involving a burst hydraulic jack pipe occurred on December 20, 2024, which caused a loading/discharging delay of 4–5 hours due to a failure in the hatch opening system. The primary causes were corrosion on the hydraulic connection pipes and dirty oil filter conditions, which triggered extreme pressure. The use of an Ultrasonic Tightness Tester proved to be more effective and accurate in detecting leaks early without damaging the cargo compared to conventional methods. In conclusion, disciplined preventive maintenance on the hydraulic system and tightness components is crucial to prevent financial losses due to demurrage penalties and to ensure the smooth operation of the vessel.